Mengeksplorasi Hubungan Orientasi Pembelajaran, Persepsi Dukungan Organisasi, dan Perilaku Kerja Inovatif pada Karyawan Management Trainees: Exploring the Relationship between Learning Orientation, Perceived Organizational Support, and Innovative Work Behavior on Management Trainees - Resta Maharani Adila Putri; Aditya Nanda Priyatama; Pratista Arya Satwika (Universitas Negeri Surabaya, 2021)
Companies must prepare their workers so they can have a competitive advantage in order to face the industrial revolution 4.0 by increasing innovative work behavior. Innovative work behavior is influenced by internal and external factors, two of which are learning orientation and perceived organizational support. However, there are only few studies that examine the relationships of internal and external factors together with innovative work behavior. The purpose of this study was to explore the relationships between learning orientation, perceived organizational support, and innovative work behavior on management trainees in a state-owned construction company. A sample of 91 respondents were selected using a simple random sampling. Data were collected using the scales of innovative work behavior, learning orientation, and perceived organizational support, and analyzed using multiple linear regression. The results show that there is a positive significant correlation between learning orientation, perceived organizational support, and innovative work behavior simultaniously. The positive and significant correlation is also found in the partial relationships between learning orientation and innovative work behavior, as well as between perceived organizational support and innovative work behavior. Keywords: Innovative work behavior, learning orientation, organizational support Abstrak: Perusahaan harus mempersiapkan pekerjanya agar dapat memiliki keunggulan kompetitif untuk menghadapi revolusi industri 4.0 dengan meningkatkan perilaku kerja inovatif. Perilaku kerja inovatif dipengaruhi oleh faktor internal dan eksternal, dua diantaranya adalah orientasi pembelajaran dan persepsi dukungan organisasi. Namun masih sedikit penelitian yang meneliti hubungan faktor internal dan eksternal secara bersama-sama dengan perilaku kerja inovatif. Penelitian ini bertujuan untuk mengetahui hubungan antara orientasi pembelajaran dan persepsi dukungan organisasi dengan perilaku kerja inovatif pada karyawan management trainee di sebuah perusahaan pemerintah bidang konstruksi. Sampel penelitian berjumlah 91 karyawan yang diseleksi menggunakan simple random sampling. Data dikumpulkan menggunakan skala perilaku kerja inovatif, orientasi pembelajaran, dan persepsi dukungan organisasi, dan dianalisis menggunakan regresi linear berganda. Hasil penelitian menunjukkan terdapat hubungan signifikan antara orientasi pembelajaran dan persepsi dukungan organisasi dengan perilaku kerja inovatif. Hasil analisis juga menunjukkan bahwa terdapat hubungan positif signifikan baik antara orientasi pembelajaran dengan perilaku kerja inovatif, maupun antara persepsi dukungan organisasi dengan perilaku kerja inovatif.